2022
DOI: 10.18502/tim.v7i4.11495
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils Composition, Antibacterial Activity and Toxicity Study of Artemisia Species Growing in Ethiopia

Abstract: Artemisia essential oils have been used in flavors, scents, mice repellents, cleansers, beauty care products, fragrances, and conventional pharmaceuticals. This work analyzed the phytoconstituents, in vitro antibacterial activity, and toxicity of essential oils of three Artemisia species growing in Wolaita, Ethiopia. GC-MS has been used to analyze chemical composition. In vitro antibacterial activity was assessed by disc diffusion and broth dilution techniques. The MTT assay was used to conduct toxicity studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The result obtained herein for the extract is inferior compared with the literature reports. 38 However, the antibacterial activity reported for the essential oil by Bibiso et al, was found to be in good agreement with our findings. 39 All of the isolated compounds displayed weak antibacterial activity against the tested microorganisms, except for compounds 3 , 4 , and 6 , which showed moderate activity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The result obtained herein for the extract is inferior compared with the literature reports. 38 However, the antibacterial activity reported for the essential oil by Bibiso et al, was found to be in good agreement with our findings. 39 All of the isolated compounds displayed weak antibacterial activity against the tested microorganisms, except for compounds 3 , 4 , and 6 , which showed moderate activity.…”
Section: Resultssupporting
confidence: 93%
“…coli) with an IDZ range of 6.1 ± 0.3 to 9.30 ± 0.20 mm. The result obtained herein for the extract is inferior compared with the literature reports . However, the antibacterial activity reported for the essential oil by Bibiso et al, was found to be in good agreement with our findings .…”
Section: Resultssupporting
confidence: 70%